2017
DOI: 10.1002/prca.201700131
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Reaction Monitoring Mass Spectrometric Method for Analysis of Potential CSF Biomarkers for Alzheimer's Disease

Abstract: Scope: The aim of this study was to develop and evaluate a parallel reaction monitoring mass spectrometry (PRM-MS) assay consisting of a panel of potential protein biomarkers in cerebrospinal fluid (CSF). Experimental design: Thirteen proteins were selected based on their association with neurodegenerative diseases and involvement in synaptic function, secretory vesicle function, or innate immune system. CSF samples were digested and two to three peptides per protein were quantified using stable isotope-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
100
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 82 publications
6
100
2
Order By: Relevance
“…Several of these proteins, including VGF, CHGA, SCG2, CysC, and β 2 M, have been suggested in previous studies to be involved in AD pathology [12][13][14][22][23][24][25][26][27][28]. A pilot study that we performed after developing the PRM panel showed promising results, with lower levels for several proteins in patients with AD dementia compared with control subjects [29]. The aims of the present study were to validate this panel of proteins in a larger and independent cohort, as well as to investigate whether the panel has potential for distinguishing patients with prodromal AD and patients with AD dementia from cognitively healthy subjects.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Several of these proteins, including VGF, CHGA, SCG2, CysC, and β 2 M, have been suggested in previous studies to be involved in AD pathology [12][13][14][22][23][24][25][26][27][28]. A pilot study that we performed after developing the PRM panel showed promising results, with lower levels for several proteins in patients with AD dementia compared with control subjects [29]. The aims of the present study were to validate this panel of proteins in a larger and independent cohort, as well as to investigate whether the panel has potential for distinguishing patients with prodromal AD and patients with AD dementia from cognitively healthy subjects.…”
Section: Introductionmentioning
confidence: 80%
“…The sample preparation and acquisition methods for PRM analysis are described in detail elsewhere [29]. For the present study, we used the same sample preparation and MS methods, with minor modifications as described below.…”
Section: Parallel Reaction Monitoring Ms Panelmentioning
confidence: 99%
See 3 more Smart Citations